The role of growth aspirations in SMME financing decisions - Belinda Rathogwa; Jabulile Msimango-Galawe (Cogent Business & Management, 2023)
The literature suggests that growth aspirations positively influence SMME access to finance. However, a knowledge gap remained concerning the role of growth aspirations in SMME financing decisions. This study explored the role of entrepreneurs' growth aspirations in their decision to apply for external finance. In addition, the study investigated the effect of intention to apply on entrepreneurs taking action to apply; and the effect of growth aspirations on entrepreneurs' intentions and actions. We conducted in-depth interviews with 14 South African entrepreneurs. In parallel, an online survey collected quantitative data from 185 South African entrepreneurs conveniently sampled on LinkedIn, Facebook and WhatsApp. Interview findings suggest that growth aspirations motivate entrepreneurs to seek external finance. The evidence indicates that intention to apply for external finance has a positive effect on entrepreneurs taking action to apply. However, we found no empirical support for growth aspirations positively affecting intention to apply or entrepreneurs taking action to apply. We propose that future research investigates a mediating effect wherein perceived desirability mediates the effect of growth aspirations on entrepreneurs' intention to apply for external finance. An improved understanding of the role of growth aspirations in SMME financing decisions can support policymakers and finance providers in guiding entrepreneurs who need external finance to grow their businesses.
Keywords: 650; entrepreneurship; financing decisions; growth aspirations; intention; SMME